Perú: comedores populares - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
IFPRI analyzed Peru’s comedores populares (community kitchens) and associated programs to .identify lessons for future urban projects. Under Project Leader, James Garrett, IFPRI’s study reviewed the operational experiences of PRODIA based on interviews with participants and CARE staff in Lima. The experiences of PRODIA offer lessons, which are described in this study.